The Volunteer Management Handbook : Leadership Strategies for Success. - Connors, Tracy Daniel (John Wiley & Sons, 2011)
Completely revised and expanded, the ultimate guide to starting-and keeping-an active and effective volunteer program Drawing on the experience and expertise of recognized authorities on nonprofit organizations, The Volunteer Management Handbook, Second Edition is the only guide you need for establishing and maintaining an active and effective volunteer program. Written by nonprofit leader Tracy Connors, this handy reference offers practical guidance on such essential issues as motivating people to volunteer their time and services, recruitment, and more. Up-to-date and practical, this is the.